Relationship between profitability and dividend payout from industrial companies listed at Dar es Salaam Stock Exchange, Tanzania - James Chindengwike (Journal Of Management Analytical and Solution (JoMAS), 2025)
The creation of profits is necessary in order to distribute dividends to shareholders after investment. Previous studies focused on dividend payments and macroeconomic conditions. The aim of this paper is to investigate the connection between profitability and dividend pay-out in Tanzanian industrial companies that are listed on the Dar es Salaam Stock Exchange (DSE). The study used a panel data research design and a quantitative technique. The research conducted from 2009 to 2023, 105 firm-year data points from seven industry categories were analyzed. The study was to compile significance data through documentary review. Panel data regression was used to evaluate the research data both descriptively and inferentially. The findings of the research showed a strong positive association (P < 0.005) between manufacturing firms' profitability and dividend payout. All things considered; the findings indicate that industrial enterprises listed on the DSE are primarily motivated by profit. The study suggests that manufacturing companies should raise their profitability to attract more capital and raise the dividend payment ratio.